2015
DOI: 10.1016/j.neurobiolaging.2015.06.013
|View full text |Cite
|
Sign up to set email alerts
|

ATXN2 is a modifier of phenotype in ALS patients of Sardinian ancestry

Abstract: Intermediate-length CAG expansions (encoding 27–33 glutamines, polyQ) of the Ataxin2 (ATXN2) gene represent a risk factor for amyotrophic lateral sclerosis (ALS). Recently, it has been proposed that ≥31 CAG expansions may influence ALS phenotype. We assessed whether ATXN2 intermediate-length polyQ expansions influence ALS phenotype in a series of 375 patients of Sardinian ancestry. Controls were 247 neurologically healthy subjects, resident in the study area, age- and gender-matched to cases. The frequency of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 17 publications
3
19
0
Order By: Relevance
“…Also, the presence of at least 1 minor allele of the rs3011225 SNP located on chromosome 1p34.1 was associated with earlier age of onset in a meta‐analysis of 13 GWAS cohorts . Finally, the presence of an intermediate CAG repeat expansion in the ATXN2 gene not only is a risk factor for ALS but also is associated with a spinal phenotype and reduces survival by 1 year …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Also, the presence of at least 1 minor allele of the rs3011225 SNP located on chromosome 1p34.1 was associated with earlier age of onset in a meta‐analysis of 13 GWAS cohorts . Finally, the presence of an intermediate CAG repeat expansion in the ATXN2 gene not only is a risk factor for ALS but also is associated with a spinal phenotype and reduces survival by 1 year …”
Section: Discussionmentioning
confidence: 98%
“…29 Finally, the presence of an intermediate CAG repeat expansion in the ATXN2 gene not only is a risk factor for ALS 24 but also is associated with a spinal phenotype and reduces survival by 1 year. 30,31 In summary, we used a large population-based cohort of ALS patients to show that functional variants of the CX3CR1 gene potentially influence ALS survival. A limitation of our study is that it is based on a candidate-gene approach.…”
Section: Discussionmentioning
confidence: 99%
“… 82 This finding is supported by an Italian study, where additionally <31 repeats were associated with spinal onset ALS and a shorter survival. 83 …”
Section: Other Rna-processing Genes Associated With Alsmentioning
confidence: 99%
“…Some genes are not only risk factors, but they may also be survival modifiers. Several studies have shown that UNC13A [3,57,58,] and ATXN2 [59,60,61] are associated with shorter survival in ALS. The type of mutation lying in the TARDBP super rich glycine-residue domain was associated with the worst survival [62 ].…”
Section: Reviewmentioning
confidence: 99%